Methodology paper: a novel phantom setup for commissioning of scanned ion beam delivery and TPS - Jäkel, Oliver; Ackermann, Benjamin; Ecker, Swantje; Ellerbrock, Malte; Heeg, Peter; Henkner, Katrin; Winter, Marc C. (Radiation oncology, 2019)
Commissioning of treatment planning systems (TPS) and beam delivery for scanned light ion beams is an important quality assurance task. This requires measurement of large sets of high quality dosimetric data in anthropomorphic phantoms to benchmark the TPS and dose delivery under realistic conditions.